1970
DOI: 10.4141/cjps70-070
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Leaf Water Status of Barley and Soil Water

Abstract: Total water potential of barley (Hordeum vulgare L.) leaves from plants grown under greenhouse and growth chamber conditions was divided into pressure and osmotic potential components, and their relationship to leaf relative water content was determined. Pressure potential approached zero at a water potential of about −32 bars, and a relative water content of about 65%. A change in the elasticity of leaves occurred at about 2 bars pressure potential and about −12 bars water potential. First visible wilting was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…A constant transpiration rate of 0.05 gjcm 2 jday was reached at about 50% relative water content. A similar pattern was observed for barley (Hordeum vulgare L.) by Millar, Duysen, and Norum (12) and agrees with reported rapid increases in the stomatal resistance of snap beans (Phaseolus vulgaris L.) as the leaf water potential drops below -11 atm (9). At any leaf water status the transpiration rate was higher as the evaporative demand increased, possibly clue to decreased stomatal and cuticular resistance to water movement (8,15).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A constant transpiration rate of 0.05 gjcm 2 jday was reached at about 50% relative water content. A similar pattern was observed for barley (Hordeum vulgare L.) by Millar, Duysen, and Norum (12) and agrees with reported rapid increases in the stomatal resistance of snap beans (Phaseolus vulgaris L.) as the leaf water potential drops below -11 atm (9). At any leaf water status the transpiration rate was higher as the evaporative demand increased, possibly clue to decreased stomatal and cuticular resistance to water movement (8,15).…”
Section: Resultssupporting
confidence: 84%
“…At leaf water contents between 93 and 97%, the slope of the leaf water characteristic changed drastically. Millar et al (12) found a similar change for barley leaves and calculated that at high relative water contents the turgor pressure dropped rapidly compared with the osmotic pressure. At lower relative water contents the reverse was true.…”
Section: Discussionmentioning
confidence: 71%
“…6) shows one way in which wheat can adapt to water stress. Large decreases in ijr n with decreasing \jr ly generally by amounts sufficient to keep \jr v positive, have been found in other species growing in drying soils (Gavande & Taylor, 1967;Millar, Duysen & Norum, 1970;Sanchez-Diaz & Kramer, 1973;Jones & Turner, 1978).…”
Section: Discussionmentioning
confidence: 72%
“…Further evidence of significant rhizosphere potential gradients comes from the slow recovery of ijf l overnight (Fig. 9), a phenomenon also observed in wheat by Campbell & Campbell (1974) and in other plants by Klepper (1968), Jordan (1970), Millar et al (1970) and Jordan & Ritchie (1971). The simplest postulate is slow equilibration of the potential at the root surface with that of the bulk soil.…”
Section: Discussionmentioning
confidence: 73%
“…Table 5 demonstrate significantly higher liije^j and RWC in the current season's needles than in the previous season's needles. A reasonable explanation of these differences may be a combined effect of (1) a larger amount of storage material (dry matter) in the older needles, decreasing their osmotic (Millar et aL 1970) and matric potentials, and (2) a decreased cell wall elasticity resulting from the dry matter increase (Knipling 1967), leading to a greater reduction in pressure potential.…”
Section: Discussionmentioning
confidence: 99%